1989
DOI: 10.1111/j.1469-8137.1989.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar uptake and invertase activity in Dendrobium tissues

Abstract: S U M M .'\ R YLJndifferentiiited and differentiated tissues ot" Dcudrobitim exhibited no difference in their preference for sugars. The uptake of sugars was more rapid by undifferentiated tissue. I-'ructose provided the best carbon source for botli tissues. Sucrose was hydrolysed before it was taken up, as the result of invertase acti\ ity. Both acid and alkaline invertase were present and invertase activity was detected in the soluble and cell wall traction. There was a gratlual increase in invertase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Hew and Mah (1989) reported that the percentage increase in dry matter of differentiated Dendrobium Multico White tissues grown in vitro was higher at 2% than at 1% sucrose. Vaz (2002), on the other hand, detected a significant decrease in the dry matter of Psygmorchis pusilla shoots grown in vitro in sucrose concentrations up to 6%.…”
Section: Resultsmentioning
confidence: 97%
“…Hew and Mah (1989) reported that the percentage increase in dry matter of differentiated Dendrobium Multico White tissues grown in vitro was higher at 2% than at 1% sucrose. Vaz (2002), on the other hand, detected a significant decrease in the dry matter of Psygmorchis pusilla shoots grown in vitro in sucrose concentrations up to 6%.…”
Section: Resultsmentioning
confidence: 97%
“…3). Contradictory results on the effect of autoclaved fructose as a carbon source (Oka & Ohyama 1986;Chauvin & Salesses 1988;Hew & Mah 1989;Welander et al 1989;Borkowska & Szczerba 1991;Moncousin et al 1992) are probably due to differences in the sensitivity of plant species to the degradation products formed as a result of autoclaving, such as furfural and hydroxymethylfurfural (Hsiao & Bornman 1989;Uosukainen & Vasara 1992;Druart & de Wulf 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A preferência pela frutose em relação à sacarose, como fonte de carbono, por algumas espécies e tecidos, pode estar relacionada à necessidade de as células excretarem a enzima invertase ao meio de cultivo, visando à hidrólise da sacarose antes da absorção da fonte de carbono (Hew & Mah, 1989). No presente experimento com P. glomerata, verificou-se que a sacarose foi a melhor fonte de carbono para o crescimento; portanto, essa espécie não apresenta dificuldades em absorver a sacarose diretamente do meio e/ou também seus produtos de hidrólise.…”
Section: (D)unclassified